An empirical study in the influencing factor on the Iranian online shopping behavior: a theory of planned behavior approach - Sara, Temouri (PHINISI, 2025)
The rapid growth of e-commerce in Iran has led to an increasing interest in understanding the factors influencing Iranian consumers' online shopping behavior. This study applies the Theory of Planned Behavior (TPB) to examine the key determinants affecting consumers' online purchasing decisions. Through an empirical approach, data was collected from a sample of Iranian online shoppers and analyzed using quantitative methods. The findings reveal that attitude, subjective norms, and perceived behavioral control significantly influence online shopping intentions, with trust and perceived risk playing moderating roles. Additionally, demographic factors such as age, gender, and internet literacy were found to impact shopping behavior. The study provides theoretical insights and practical implications for e-commerce businesses seeking to enhance consumer trust and engagement in Iran’s digital marketplace.